Analisis Kualitas Produk di PT. Adi Kuasa Gasindo Medan - Zeky Ricardo; Sutarno; Dewi Anggraini (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
PT. Adi Kuasa Gasindo, Medan is a provider engaged in the transmission and distribution of natural gas. The formulation of the problem in this research is “How is the product quality applied to PT. Adi Power of Gasindo, Medan?” The purpose of the study was to find out what was applied at PT Adi Power Gasindo Medan. The research method that the author uses is a qualitative descriptive research method. The data collection technique used by the author is a structured interview technique. From the results of interviews with the warehouse head and admin staff, information was obtained that the product quality at PT. Adi Power of Gasindo is still not good. improve quality control so that no product damage is presented to customers, give customers the opportunity to provide input on new products, as well as provide advance warning about damage that can cause large losses, without having to burden employees